Polymorphisms in JMJD1C are associated with pubertal onset in boys and reproductive function in men. Issue 1 (December 2017) - Mørup, Nina; Busch, Alexander; Bang, Anne; Nordkap, Loa; Nielsen, John; Rajpert-De Meyts, Ewa; Juul, Anders; Jørgensen, Niels; Almstrup, Kristian
Abstract JMJD1C, a member of the Jumonji-domain containing histone demethylases protein family, has been associated with levels of sex-hormone binding globulin (SHBG) and testosterone in men, and knock-out rodent models show age-dependent infertility. The objective of this study was to investigate whether single nucleotide polymorphisms (SNPs) nearbyJMJD1C are associated with pubertal onset in boys and with male reproduction. 671 peri-pubertal boys, 1, 027 young men, 315 fertile men, and 252 infertile men were genotyped for twoJMJD1C SNPs (rs7910927 and rs10822184). rs7910927 and rs10822184 showed high linkage. Boys with the rs7910927 TT genotype entered puberty 3.6 months earlier than their peers (p = 2.5 × 10−2 ). In young men, the number of T alleles was associated with decreased levels of SHBG, follicle-stimulating hormone (FSH), testosterone, and testosterone x luteinizing hormone, as well as increased levels of Inhibin B, Inhibin B/FSH ratio, and testis size. No significant associations with semen parameters were observed and the genotype distribution was comparable among fertile and infertile men. In conclusion, genetic variation in the vicinity ofJMJD1C had a surprisingly large impact on the age at pubertal onset in boys as well as levels of reproductive hormones and testis size in men, emphasizing the relationship between JMJD1C and reproductive functions.